Guest

In Solution of Traingle, How doess acos^2(C/2) + ccos^2(A/2)= 3b/2 become a(1+cosC) + c(1+cosA)?

In Solution of Traingle,
How doess acos^2(C/2) + ccos^2(A/2)= 3b/2
become a(1+cosC) + c(1+cosA)?

Grade:12

1 Answers

Rinkoo Gupta
askIITians Faculty 80 Points
8 years ago
acos2(C/2)+c
cos2(A/2)=3b/2
2acos2(C/2)+2ccos2(A/2)=3b
a(1+cosC)+c(1+cosA)=3b
Using formula
2cos2x=1+cos2x

Thanks & Regards
Rinkoo Gupta
AskIITians Faculty

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free